Perfil de voláteis, de aroma, de ácidos graxos e de tocoferóis em óleos obtidos por prensagem a frio de resíduos agroindustriais de mangaba (Hancornia speciosa) - Silva, Gleise Kely da Cruz (2018)
Sergipe produces annually near 352 tons of Mangaba (Hancornia speciosa), and is the chief mangaba’s producer in Brazil. Most part of this production is industrialized as frozen pulp, being this activity very important to the state’s economy. However, mangaba’s industrialization generates wastes that if not properly processed, cause environmental problems. A considerable amount of mangaba’s agroindustrial waste consists of seeds showing high lipid content. The aim of this work was to evaluate the potential of the seeds from mangaba’s agroindustrial waste, to produce oil for culinary and/or cosmetic applications. Mangaba’s seeds obtained from an agroindustry located in Aracaju/SE, were dried, ground and submitted to cold pressing in an hydraulic press under 30 tons. The oil obtained was characterized regarding its relative density, moisture content, indexes of refraction, acidity, saponification and iodine, and fatty acid profile. The volatile compounds of the oil’s headspace were identified in comparison to the processed pulp. They were isolated through a solid phase microextraction technique (SPME), separated both in an HP-5MS and in a DB-Wax capillary column, and analyzed in a GC-MS system. The isolation conditions were optimized using a factorial design 2 2 (DCCR), whose independent variables were the adsorption temperature (40ºC- and 80ºC) and the extraction time (20 – 60 min). The data were evaluated by Response Surface Methodology and Desirability Function. Trained judges generated the oil’s aroma profile in comparison to three commercial cold pressed oils, through quantitative descriptive analysis (QDA). The sensory data were evaluated by ANOVA, Tukey (p≤0,05) and Principal Component Analysis (PCA). The results showed that the oil extraction process from the mangaba’s seeds containing 4,7% humidity and 16,7% of lipid, presented 37% yield. The extracted oil showed relative density of 0,91 g.cm-3, acidity of 5,47 mgKOH.g-1, saponification index of 193,00 mgKOH.g-1 and iodine value of 69 cgI2.g-1. The oil´s fatty acid profile was similar to the olive oil; it contained 72% of unsaturated fatty acids and oleic acid as the major fatty acid (63,7%). Among the tocopherols, only α-tocopherol was identified in the oil; its concentration was 6,17mg/100g. The best isolation condition of the oil´s volatiles was predicted as 57,2ºC and 60 min of fiber exposition. Eighty (80) volatiles were identified in the oil and 82 in the processed pulp. Esters formed the major chemical class in the oil, as well as in the pulp, corresponding to respectively 56,7% and 70,9% of the total area of the chromatogram. The alcohols were the second major chemical class representing 13,9% and 18,4% of the total chromatogram area of the oil and the processed pulp, respectively. The mangaba seed’s oil presented a distinguished aroma which differed from the others cold pressed oils analyzed due to a higher intensity (p≤ 0,05) of notes described as mangaba’s seed, sweetness, frutal, freshness and caramelized banana. The results indicate that the mangaba’s seed is suitable for cold pressing oil extraction. Due to its similarity to the olive oil regarding their fatty acid profiles, and to its esters content, which are volatiles usually associated to desirable fruit aroma, the mangaba´s oil has potential to be used in culinary and by the cosmetic industry. However, complementary studies must be performed in order to ensure the oil safety with respect to its toxicity and allergenicity before its use in the suggested applications.